Medication-related osteonecrosis of the jaw in cancer patients: Case series and review of the current literature - Reyes Castillo, Karen Maciel (2022)
Currently, a large proportion of cancer patients are treated with bone modifying agents (BMA). In this regard, the increase in the prescription of these drugs has led to concerns about the increment of osteonecrosis of the jaws. This article describes four patients with BMA cancer treatments requested dental evaluation at our institution due to pain and swelling of the mandibular bone after tooth extraction, tooth loss, or unknown risk factor. Oral and radiographic evaluation reveals MRONJ at different clinical stages according to the American Association of Oral and Maxillofacial Surgeons (AAOMS) classification. Some patients underwent abscess drainage, oral cleaning, and antibiotic therapy with complete recovery. Follow-up achieved treatment success in all patients. That is why we emphasize the importance of the prompt establishment of appropriate treatment and emphasize the avoidance of dental procedures during BMA therapy.